Effects of Planting Density and Concentration of NPK Fertilizer on the Growth of Potted Chrysanthemum (Chrysanthemum morifolium Ramat) - Feby Steviani Anugrah Ramadhan; Setyono Setyono; Evi Dwi Sulistya Nugroho (JURNAL AGRONIDA, 2018)
Chrysanthemum is an ornamental plant that people likes, grows the whole year, and hashigh economic value. This study was aimed at assessing the effects of planting density andconcentration ofNPK fertilizer on the growth of potted chrysanthemum. The study was conductedin a plastic house at the Indonesian Ornamental Crops Research Institute (IOCRI), Cipanas,Cianjur, West Java from March to June 2017. Shoot cuttings of ±7 cm of potted chrysanthemum ofAvanthe Agrihorti cultivar were used. A completely randomized design in a factorial pattern withfactors was used. The first factor was planting density and the second factor was concentrationofNPK (16:16:16) fertilizer. The planting density consisted of 5, 6, and 7 shoot cuttings andconcentrationof NPK fertilizer were 150, 200, 250, and 300 ppm. Results showed that plantingdensity significantly affected stem diameter, number of buds, and width of canopy. No effectconcentrationof fertilizer was found on all variables.Keywords: potted chrysanthemum, planting density, NPK fertilizer